The Study Framework for Improving Oversight Function of the Thai Public Accounts Committee through the lens of Institutional Theory - Trakuldist, Chinnapong; Suntharanurak, Sutthi (Journal of Thai Ombudsman, 2024)
The relationship between Public Accounts Committees (PAC) and Supreme Audit Institutions (SAI) is crucial for promoting accountability in the public financial management system. Their roles are closely connected, as the PACs are the primary stakeholders and recipients of SAIs' services, while SAIs also rely on parliamentary interests to influence the government to implement their recommendations. However, in Thailand, many studies found limited collaboration between the Thai PAC and SAI Thailand in scrutinizing the execution of the budget thoroughly or assessing government performance. The lack of effective collaboration could stem from many factors, especially an unclear mandate of the PAC, which allows the committee to rely on discretion, not audit results when performing oversight functions. Consequently, this could adversely affect Thai public financial management, as SAI Thailand found increasing trends of incompliance, misuse, and mismanagement of public funds caused by similar issues such as incorrect contracts, unuse of procured items, or unachieved objectives. Therefore, the objective of this paper is 1) to emphasize the importance and the contributions of studying institutional contexts through a systematic review of relevant literature about Public Account Committees and institutional theory, and 2) to provide a framework for exploring institutional contexts of the Thai PAC. Consequently, this would possibly improve the oversight function of other committees and the relationship with Supreme Audit Institution of Thailand.